Alterations of physical performance in elite male handball players during a season - Povoas, S.; Ascensao, A.; Magalhaes, J.; Seabre, A.; Oliveira, E.; Soares, J.; Rebelo, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Handball is an intermittent sport that implies specific endurance and high-intensity physical performance demands (Povoas et al., 2012). To cope with these demands during an entire competitive season, handball players are submitted to training and competition sets, which may induce variations in physical performance levels. We therefore aimed to analyse the effects of training and competition during an entire season on elite male handball players anthropometric and physical profile. Methods: Sixty-three players from six teams of the Portuguese Handball Professional Male League were evaluated three time points throughout the season (pre-season (T0), pre-competitive period (T1) and competitive period (T2)). The players performed the Yo-Yo Intermittent Endurance Test.level 2 (YYIE2), the countermovement (CMJ) and squat jumps, a straight sprint test (5 and 20 m), a sprint test with changes of direction (COD), and the running-based anaerobic sprint test (RAST) (for refs see Povoas et al., 2012). Results: Significant increases were observed in YYIE2 and jump performance from T0 to T1 time points, although CMJ height decreased in T2 (p.0.05). There were no significant changes in the anthropometric profile as well as in straight sprint performance throughout the season. Nevertheless, COD performance increased in T2 and also in T1 when compared to T0 (p.0.05). RAST-related fatigue index decreased in T2 when compared to T0 (p<0.05). Discussion: Our results show that training and competition induced alterations in physical capacities evaluated during a season, which is in accordance with other studies (Gorostiaga et al., 2006; Hakkinen, 1988). Training sessions and competitive matches favourably modulated specific endurance, repeated sprint and power-related abilities throughout the season, with the exception of CMJ. The specific pattern of handball movements and actions require particular neuromuscular demands also targeting positive influences on COD throughout the season, an agility-related test closely related to the ability to perform acceleration-deceleration movements, which in turn are associated to eccentric muscle contractions.